Why does frugality influence the recycling intention of waste materials? - Wang, Hong; Bai, Rubing; Zhao, Haibo; Hu, Zhichen; Li, Yan (Frontiers in Psychology, 2023)
Waste recycling significantly impacts the sustainable development of society and the ecological environment, contributing to a vital role within the waste management hierarchy. This paper presents a research model that investigates the influence mechanism of consumers' frugality on their recycling intentions. This study collected 420 valid samples to test the model with regression analysis. The empirical results show that consumers' frugality exerts a direct and positive effect on their recycling intention. Except for the positive direct eﬀect, perceived value mediates the relationship between frugality and recycling intention. Besides, environmental concern strengthens the positive relationship between frugality and recycling intention. The findings of this study can better explain the recycling intention, thereby providing a basis for the government and enterprises to formulate policies and measures to promote recycling behavior.